Ćwiczenia kształtujące w profilaktyce wad postawy u dzieci w wieku wczesnoszkolnym - Michał Bąkowicz (Lesya Ukrainka Volyn National University, 2016)
One of the most important tasks of physical education ina secondary school is posture disorders prevention among junior pupils. In the process of an experiment different gymnastic exercises were done, they were chosen individually for every pupils according to the condidtion of his posture and were done systematically during lessons of physical education. Conducted reseach has shown their effectiveness. Body posture among children from the experimental group was much better than control group.